1999
DOI: 10.3168/jds.s0022-0302(99)75323-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Milk Protein Polymorphism and First Lactation Milk Production Traits in Finnish Ayrshire Cows

Abstract: Genotypic effects of beta-casein (CN), kappa-CN, and beta-lactoglobulin (LG) on milk, fat, and protein production and fat and protein percentages were estimated for 18,686 Finnish Ayrshire cows in first lactation using an animal model. Casein genotype effects were estimated including individual beta-CN and kappa-CN simultaneously in a model and then as composite beta-kappa-CN. The A2 allele of beta-CN and the A allele of kappa-CN, as well as the A1 allele of beta-CN and the B or E allele of kappa-CN, appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
74
2
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 17 publications
13
74
2
4
Order By: Relevance
“…High yield characteristics were also associated with genotypes BBAA, AABB and AAAB. This is in agreement with Ikonen et al (1999b), who found that CSN3 alleles E and A increase milk yield but decrease protein content. The highest protein content was found in the genotype combinations BBAA, ABBB and ABAB, which illustrates the effect of CSN3 allele B on increasing protein content (Ikonen et al, 1999b;Kučerová et al, 2006).…”
Section: Fifteen Genotype Combinations Of Csn3 Andsupporting
confidence: 82%
See 1 more Smart Citation
“…High yield characteristics were also associated with genotypes BBAA, AABB and AAAB. This is in agreement with Ikonen et al (1999b), who found that CSN3 alleles E and A increase milk yield but decrease protein content. The highest protein content was found in the genotype combinations BBAA, ABBB and ABAB, which illustrates the effect of CSN3 allele B on increasing protein content (Ikonen et al, 1999b;Kučerová et al, 2006).…”
Section: Fifteen Genotype Combinations Of Csn3 Andsupporting
confidence: 82%
“…This is in agreement with Ikonen et al (1999b), who found that CSN3 alleles E and A increase milk yield but decrease protein content. The highest protein content was found in the genotype combinations BBAA, ABBB and ABAB, which illustrates the effect of CSN3 allele B on increasing protein content (Ikonen et al, 1999b;Kučerová et al, 2006). Similarly, Kaminski et al (2002) reported the highest protein content as well as fat content associated with genotype combinations ABBB and ABAB.…”
Section: Fifteen Genotype Combinations Of Csn3 Andsupporting
confidence: 82%
“…For the first extra QTL, the position estimates were close to the marker ILSTS97, which was also reported by Moisio et al (2000) to affect the PP trait. For the second, the estimated position was close to CSN3 and CSN1, as reported by many researchers (Velmala et al, 1995;Maki-Tanila et al, 1998;Leone et al, 1998;Ikonen et al, 1999), and also close to AFR227, as reported by Velmala et al (1999), and to BP7, as reported by Ashwell et al (1998) and Schnabel et al (2005), all of which were found to affect the PP trait. The variance component model can be written as…”
Section: Discussionsupporting
confidence: 64%
“…A positive effect of κ-CN B and β-Lg B alleles on the protein content was also reported by Ikonen et al (1999) and Miceikiene et al (2005). It was proved that A variant of β-Lg compared to B variant had higher protein (Ng-Kwai-Hang, 1998) and fat contents.…”
mentioning
confidence: 56%
“…The effect of the κ-CN/β-Lg variants and herd on milk composition and technological properties of milk (GLM analysis) (Chrenek et al, 1998;Ng-Kwai-Hang, 1998;Ikonen et al, 1999;Miceikiene et al, 2005). Our results agree with these conclusions.…”
Section: Resultsmentioning
confidence: 99%